2017
DOI: 10.1016/j.otsr.2016.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Proximal femoral fractures in centenarians. A retrospective analysis of 39 patients

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“… 10 Thirty-day mortality has been reported to be approximately 8–34% in older patients. 6–8 , 11 , 12 , 18 , 23 Our findings showed that female sex, time to surgery >48 hours, baseline ambulatory capacity and cognitive function, anaesthetic risk, type of anaesthesia and peripheral nerve block, and age group were related to 30-day mortality over the entire sample. However, only the ASA score was associated with 30-day mortality in centenarians.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“… 10 Thirty-day mortality has been reported to be approximately 8–34% in older patients. 6–8 , 11 , 12 , 18 , 23 Our findings showed that female sex, time to surgery >48 hours, baseline ambulatory capacity and cognitive function, anaesthetic risk, type of anaesthesia and peripheral nerve block, and age group were related to 30-day mortality over the entire sample. However, only the ASA score was associated with 30-day mortality in centenarians.…”
Section: Discussionmentioning
confidence: 62%
“…This may be due to the higher baseline degree of cognitive impairment and dependency or the higher degree of in-hospital complications in this age group. 9 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One retrospective analysis of trauma in centenarians described a higher incidence of inpatient (19%) and 30-day mortality (33%) than our study [8] . Another case series of 12 centenarians undergoing surgery for proximal femur fracture reported a higher 1-year mortality rate (88%) [23] . These differences may have been attributable to their selection of trauma cases—invariably of higher acuity than our lower procedural risk cases—and the inclusion of centenarian trauma patients that were deemed not fit for surgery.…”
Section: Discussionmentioning
confidence: 99%